Bolsa família: os impactos dos programas de transferência de renda no cotidiano familiar - Dalt, Salete da (2010)
This dissertation presents a theoretical and methodological perspective to evaluating in a quantitative approach - a project of Assessment of the Bolsa Família Program and its Impacts on Alimentary Security. The main objective was to contribute in a critical way to the process of learning and reflection of public policies aimed at the improvement of these policies awakening to the need to learn to focus at the public to whom they are intended. The main issues discussed are organized into two axes: 1) to contextualize the Brazilian family today and the discussion of the Transfer of Income policies that resulted in the Bolsa Família Program; 2) the assessment from the perception of benefiting from Bolsa Família Program and its impacts while Income Transfer Program recorded in accordance with the familiar arrangements.